Sociological study of the relationship between religious adherence and social capital and its role in the psychological explanation of life satisfaction - Shirazi, Zeynab; Chitsaz, Mohammadali; Hejazi, Seyed Naser (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2021)
Background and Aim: Religious adherence or being religious refers to the degree of belief or adherence to the beliefs and practices of a systematic religion. Satisfaction with life indicates the satisfaction of basic human desires and needs. This research seeks to investigate the relationship between religious adherence and social capital with life satisfaction. Method: This research aims to be an applied and descriptive survey of the correlation type. The population under study is the citizens of Shahreza city between 18 and 50 years old, and 384 citizens of Shahreza were selected as the statistical sample of the study by random cluster sampling method. The research tool includes a questionnaire made by the researcher (adapted from the religiosity questionnaire of Jan Bozorgi (2018), the social capital questionnaire of Pantam (1999) and the quality of life satisfaction and enjoyment questionnaire of Endikt et al. (1993)). After collecting the data, they were analyzed using SPSS and Smart PLS statistical software, and in this regard, regression analysis and structural equation modeling were used to test the hypotheses. Results: The results of the statistical analysis of the data showed that there is a significant and moderate direct relationship between the subscale of religious adherence and life satisfaction (r=0.478, p